A Comparative Study of the Ability to Separate Isomers and Surface Properties of Leaves and Stems of Leonurus cardiaca L. Biomass - Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (WILEY-V C H VERLAG GMBH, 2025)
Inverse gas chromatography was used to investigate the isomer separation capability and surface properties of Leonurus cardiaca L. leaves and stems. The retention diagrams of the selected solvents were plotted between 303.2 and 328.2 K using the inverse gas chromatography technique. The selectivity coefficients (alpha) of the structural isomers were determined for L. cardiaca L. biomass under conditions of infinite dilution using the retention diagram. Besides, the surface properties of L. cardiaca L. biomass were investigated using inverse gas chromatography at infinite dilution. The dispersive surface energy of the adsorbent was determined using the Schultz, Dorris-Gray, Donnet-Park, and Hamieh methods. Adsorption enthalpy and Gibbs free energy were calculated using this technique. It was determined that the surface of both L. cardiaca L. leaves () and stems () exhibit acidic characteristics.
Keywords: inverse gas chromatography; isomer separation; Leonurus cardiaca L.; surface properties; INVERSE GAS-CHROMATOGRAPHY; LIQUID-CRYSTALLINE; INFINITE DILUTION; ADSORPTION; FIBERS; SILICA; ENERGY; XYLENE; Chemistry